PENDAPAT KONSUMEN TERHADAP BRAND FASHION KITC DI INSTAGRAM - Muhammad Naqsyabandi; Soedarsono, Dewi K (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
KITC believes that anything that contains humor, is unique, and fun will make it easy to consume so that it is easier for the general public to digest it. For that reason, each of their products and brands really shows that persona. Departing from this background, KITC maximizes the uniqueness of their humorous persona by turning it into one of their steps in implementing the elements contained in social media Instagram as a medium for promoting their products. This research is a research conducted to find out how the direct opinions of consumers and followers of the KITC Instagram account in providing their ideal opinion regarding several activities of Instagram elements that exist on the Instagram account of the KITC fashion brand in 2020-2022. This research is a research that uses an interpretive descriptive approach by carrying out a procession of in-depth interviews with consumers and followers of the KITC Instagram account, and linking the consumer's point of view with previous research and existing theoretical foundations. The findings and conclusions obtained from this study are that consumers and followers of the KITC Instagram account are able to provide their opinions regarding the Instagram home page element, Instagram comments element, Instagram explore element, Instagram profile element and Instagram caption element which is implemented on the KITC fashion brand Instagram account activity.